Effect of Environment on Education and Personality of a School Student: The Impact of Environment on Education, Personality, and Academic Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2014)
It  was  found from  the  present research  that  academic achievement  was  significantly affected by almost allindependent variables of the study except birth order and family type. Opennessfactor of personality was affected by independent variable of mother’seducation, gender and family size. Emotional stability factor of personalitywas significantly affected only by total home environment and family relations.Extroversion factor of personality was affected by home environment, familyrelations, mother’s education, father’s education, family’s income andsocioeconomic status. Conscientiousness factor of personality was affected byhome environment, family relations, socioeconomic status, gender and income ofthe family. Agreeableness factor of personality was affected by total homeenvironment, family relations, mother’s education and father’s education. Thusit is concluded that students’ personality factors were partially affected bythe independent variables of the study. In short we can say that with the exception of birth order and familytype, all independent variables of the study had significant effect onstudents’ academic achievements. But as far as student’s personality wasconcerned, it was only partially affected by different independent variables ofthe study. Present study found a significant effect of family relations on thetotal personality of students. Students who had good family relations, hadhighest personality mean (149.31), while those students who had poor familyrelations, their personality mean was the lowest (130.23). It means students personality was positively affected by familyrelations. Similarly family relations were found to have a significant effecton all the factors of personality studied in the present research(extroversion, emotional stability, conscientiousness, and agreeableness),except openness to experience. Statistically, openness to experience was alsoaffected by family relations, but the effect was not significant.